In Vitro Antimicrobial Activity of The Filtrate Crude Extract Produced by Aspergillus niger - A.H. Alhasan, Dhurgham; A. Husein, Husein; Q. Dawood, Ahmed (University of Thi-Qar Journal of Science, 2019)
Introduction: Aspergillus niger represents one of the fungi that can produce the secondary metabolites, including antimicrobial agents, industrial and biotechnological products. Methodology: A. niger was tested against Candida albicans on the same petri dish of potato dextrose agar at room temperature. A. niger was cultured in potato dextrose broth at 27 °C for 7 days. The fungal filtrate was separated from mycelia, and the filtrate was extracted for getting a crude blackish-brown extract. The GC-MS analysis used to identify the constituents of the extract. Results: The filtrate crude extract of A. niger exhibited the antimicrobial effects against Staphylococcus aureus, Streptococcus mutans, Escherichia coli, and Candida albicans.GC-MS analysis revealed that the extract contains [(5-methyl-2-phenylindolizine), (thiocarbamic acid, N,N-dimethyl, S-1,3-diphenyl-2-butenyl ester) and (22-beta.-acetoxy-3.beta.,16.alpha.-dihydroxy-13,28epoxyolean-2)].The extract had the toxic effect on a solution of the human red blood cells by using 300 µL of 10 mg/ml after 5 minutes while 100 µL and 200 µL of the same concentration did not appear the toxic effects during 1 hour of the testing time period. Conclusions: The extract of A. niger has the ability to produce the antimicrobial activity, so it very needs to separate its constituents into pure compounds for elucidating their chemical structure by using techniques of spectrometry. Then, the compounds can be separately testing against microbial pathogens, human normal cell to determine half lethal concentration (LC50)), and application of other biological tests such as test of LD50.